Research issues in biological inspired flying robots - Silva, Manuel (2019)
Biological inspired locomotion robotics is an area reveal-ing an increasing research and development. In spite of all the recent engineering advances, robots lack capabilities with respect to agility, adaptability, intelligent sensing, fault-tolerance, stealth, and utilization of in-situ power resources compared to some of the simplest biological organisms. The general premise of bio-inspired engineer-ing is to distill the principles incorporated in successful, nature-tested mechanisms, capturing the biomechatronic designs and minimalist operation principles from nature’s success strategies. Based on these concepts, several robots that adopt the same locomotion principles as animals, like legs for walking, fins for swimming, segmented body for creeping and peristaltic movements for worm like loco-motion, were developed in the last years. Recently, flap-ping wings robots are also stating to make their debut but there are several problems that need to be solved before they may fly autonomously. This paper analyses the ma-jor developments in this area and the directions towards future research.